Can Incorporating Brassica Tissues into Soil Reduce Nitrification Rates and Nitrous Oxide Emissions?. Issue 6 (1st November 2018) - Balvert, S. F.; Luo, J.; Schipper, L. A.
Abstract : New Zealand agriculture is composed predominantly of pastoral grazing systems; however, forage crops have been increasingly used to supplement the diet of grazing animals. Excreta from grazing animals has been identified as a main contributor of N2 O emissions. Some forage crops, such as brassicas ( Brassica spp.), contain secondary metabolites that have been identified to inhibit soil N cycling processes, and nitrification in particular. Our objective was to determine if secondary metabolites released from brassica tissues inhibited nitrification and reduced N2 O emissions when incorporated into soil, which was amended with a large amount of urea N (such as derived from urine patches deposited during grazing). Three brassica tissues (kale [ Brassica oleracea L.], turnip [ Brassica rapa L.] bulb, and turnip leaf and stem) and ryegrass ( Lolium perenne L.) tissue were incorporated into soil with and without urea solution, and N2 O, NO3 −, and NH4 + were measured during a 52‐d incubation. All brassica tissues reduced urea‐derived N2 O emissions relative to ryegrass tissues when incorporated into soil. According to the mineral N and microbial community data, this reduction, however, could not be attributed to inhibition of nitrification. Although there was less N2 O from urea in the brassica treatments, total N2 O emissions increased after incorporation of all tissue residues into soil, so this tradeoff must be explored if brassica tissues are to be considered as a tool for N2 O reduction. Core Ideas: Brassicas have been postulated to inhibit nitrification and N2 O emissions. Incorporating brassica tissues into soil reduced N2 O emissions from added urea. There was no evidence that tissue incorporation inhibited nitrification. However, addition of ryegrass and brassica tissues increased total N2 O emissions. N2 O emission tradeoffs between tissue inputs and inhibition need to be explored.